Reducing unemployment among Caribbean citizens - Bissember, Enid E. ([s.n.] [S.l.], 1995)
Focuses on the need for regional cooperation in devising strategies to deal with the problem of unemployment among young people in the Caribbean. Highlights the Caribbean Enterprise Education and Development Trust Fund.